Optimalisasi Pemanfaatan Limbah Organik Rumah Tangga melalui Pelatihan Pembuatan Kompos di Kelurahan Sumber Jaya RT 26 - Fera Gustiana; Suratul Aini; Vifty Octanarlia N; Intan Apriani; Dwi Kurnia Putri; Bagas Pratama; Sigit Surya Pratama; Fairuz Rahman (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Household organic waste remains an environmental issue in RT 26, Sumber Jaya Village, Kampung Melayu District, Bengkulu City, despite its abundant availability in the form of vegetable scraps, fruit peels, and dry leaves. This community service activity aimed to utilize this organic waste through composting training using the Asset-Based Community Development (ABCD) approach, which includes asset identification, planning, implementation, mentoring, and evaluation. The training was conducted through material delivery, demonstrations, and hands-on practice in compost production using locally available organic materials. The results showed an improvement in community understanding of organic waste management as well as basic composting skills. This is supported by questionnaire results from 10 respondents with an average score of 3.25, categorized as high, indicating a positive impact of the program. The high enthusiasm of participants during discussions and practice also reflects increased awareness of the importance of environmentally friendly waste management. Overall, the program successfully encouraged the utilization of local assets and increased community participation in sustainable household waste management.